Erythrocyte Respiratory Activity of the Mitochondrial Complex of the Black Sea Thornback Ray (Raja clavata L.) under the Influence of Certain Activators and Inhibitors In Vitro - Yuriy A. Silkin; Mikhail Yu. Silkin; Sergey M. Korotkov; Elizaveta N. Silkina; Alla Silkina (Fishes, 2022)
Global warming implies the risk of a changing oxygen regime in the seas and oceans of our planet. The mitochondrial complex of nuclear erythrocytes of cartilaginous fish, as the energy basis of blood cells, has repeatedly encountered such climatic fluctuations throughout their evolutionary history. In this regard, the features of the adaptive strategy of the erythrocyte mitochondrial complex in the thornback ray (Raja clavata L.) are of interest from the evolutionary and ecological points of view. The rate of oxygen consumption in resuspended (Ht = 25–30%) erythrocytes taken from the Black Sea thornback ray in saline was studied by the polarographic method. A high “basal” rate of respiration in the erythrocytes of the thornback ray was shown, which ranged from 10.5 to 21.6 pmol O2 min−1·106 cells. The addition of substrates of the mitochondrial respiration activators glutamate, maleate, and succinate to the erythrocyte suspension caused a 2–6-fold increase in the respiratory activity of thornback ray erythrocytes. In cases where the rate of respiration of erythrocytes was high, protonophore–dinitrophenol caused an inhibition of the activity of mitochondrial respiration. At low respiration rates of erythrocytes, its effect was opposite and caused a stimulation of mitochondrial respiration. Oligomycin caused a significant inhibition of the respiratory activity of the red blood cell suspension of the thornback ray. This suppression of cell respiration was enhanced under conditions of exposure to the permeabilization of erythrocytes with digitonin. This can be recommended as one of the ways to block the respiratory activity of erythrocytes in cartilaginous fish. Another way of effectively blocking the respiration of the mitochondrial complex of the thornback ray’s erythrocytes was the effect of the blockers rotenone and sodium azide. The peculiarity of the mitochondria of the erythrocytes of the thornback ray was the absence of the complete inhibition of respiration by sodium azide (NaN3), which is characteristic of the mitochondria of other fish species. Our data on the activation of the “respiration” of erythrocytes in fish indicate that the potential capabilities of cold-blooded and warm-blooded vertebrates have rather similar characteristics. This may indicate the initial “laying” of the architecture of the inner membrane to support the energy potential of the mitochondria of the cell.